Stochastic frontier analysis applied on Colombian universities (2019)
Knowing the efficiency of higher educational institutions is a valuable information for evaluating the educational system in general and for identifying the best practices among universities. In this study, we perform a Stochastic Frontier Analysis (SFA) to evaluate these efficiencies. For this analysis, we identified that universities behave as multi-output decision units, that is, they focus on different productive results that are condensed in latent teaching and research factors. A factor analysis is performed to estimate these latent outputs. Subsequently, two models of SFA are made using the methodology proposed by Battese and Coelli (1995). The results show that government initiatives, such as the National Accreditation Council, which encourage the production of quality products in universities, facilitate them to operate efficiently. Additionally, the geographical location of the institutions influences the mean of inefficiency.